Skills for social work practice - Mantell, Andy (Sage Publications, 2013)
aIncludes bibliographical references and index; Social work skills are essential to good practice and more important than ever following changes to the social work curriculum. Students must be able to demonstrate knowledge of core skills within policy, law as well as demonstrating empathy and good communication. This fully-revised student guide, previously published as Social Work Skills with Adults, will help to cement these skills and includes chapters on intervention, empowerment and advocacy, skills for collaborative working, self-presentation and much more